DUTOR INSTRUMENT: HISTORY, CULTURAL AND SPIRITUAL ESSENCE AND EDUCATIONAL AUTHORITY (British Journal of Global Ecology and Sustainable Development, 2026)
This article is devoted to a comprehensive study of the history, cultural-spiritual essence and educational potential of the dutor — a musical instrument that occupies a special place in the national cultural heritage of Uzbekistan and all Central Asian peoples. The article traces the historical path from the Persian etymology of the word meaning 'two strings' to the first written sources of the 15th century — the treatise 'The Canon of Musical Science and Practice' by Zaynulobidin al-Husayni. The role of the dutor in the Shashmaqam tradition, bakhshi art, and folk ceremonies, as well as its influence on the cultures of various peoples through the Silk Road, are described in detail. The instrument's contribution to national identity, moral education and aesthetic development is analyzed from a pedagogical perspective. The article is based on studies by Uzbek and world scholars, ancient treatises and modern ethnomusicological sources.